If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -12 + -3y = -2 Reorder the terms: -12 + 8y + -3y = -2 Combine like terms: 8y + -3y = 5y -12 + 5y = -2 Solving -12 + 5y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 5y = -2 + 12 Combine like terms: -12 + 12 = 0 0 + 5y = -2 + 12 5y = -2 + 12 Combine like terms: -2 + 12 = 10 5y = 10 Divide each side by '5'. y = 2 Simplifying y = 2
| 9x+8y=-16 | | 4(4x-3)=8(2x-2)+4 | | 9n-20=7 | | 6x-10=3x+5 | | 42y-7=31 | | 54=4w+2w | | 90×2/3 | | M^2+56=15m | | 54=4w | | x-3=-2+3 | | 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 | | y=0.25x+8 | | 5x+20+2x+11=115 | | 14n+3(n+5)=117 | | x^1/4(2x^3/4-x^1/4) | | (5v-3)(5v-2)=0 | | 100+2x+15-9x=5-7x+22-11x |